2016
DOI: 10.1212/cpj.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Minor ischemic stroke

Abstract: Background: Two-thirds of patients with stroke have mild deficits. The optimal triaging of these patients remains unclear. It is crucial to stratify patients based on who needs inpatient vs outpatient evaluation in a cost-effective manner. Methods: We reviewed the current literature (randomized trials, retrospective studies, case series, and case reports) on minor ischemic stroke and extrapolated evidence-based opinions and future directions on the management of minor ischemic stroke. Results:We provide eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…This is the first study to demonstrate corneal nerve and endothelial cell pathology in patients with TIA or minor IS, extending our previous findings in patients with major stroke [ 19 , 20 ]. Diabetes, hypertension, smoking, dyslipidemia [ 27 – 29 ], obesity [ 25 ] and metabolic syndrome [ 30 ] are known risk factors for stroke and are linked to cerebral white matter lesions and silent lacunar brain infarcts [ 31 ], but have limited prognostic value for recurrent stroke in patients with TIA and minor IS [ 4 ]. Impaired cerebral reactivity has been associated with the risk of subsequent stroke in patients with TIA [ 32 , 33 ], and smoking, hypertension, diabetes and cholesterol are related to altered CBF in patients with TIA and minor stroke [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to demonstrate corneal nerve and endothelial cell pathology in patients with TIA or minor IS, extending our previous findings in patients with major stroke [ 19 , 20 ]. Diabetes, hypertension, smoking, dyslipidemia [ 27 – 29 ], obesity [ 25 ] and metabolic syndrome [ 30 ] are known risk factors for stroke and are linked to cerebral white matter lesions and silent lacunar brain infarcts [ 31 ], but have limited prognostic value for recurrent stroke in patients with TIA and minor IS [ 4 ]. Impaired cerebral reactivity has been associated with the risk of subsequent stroke in patients with TIA [ 32 , 33 ], and smoking, hypertension, diabetes and cholesterol are related to altered CBF in patients with TIA and minor stroke [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transient Ischemic Attack [ 1 ] and minor ischemic stroke (IS) share similar pathophysiology to stroke [ 3 ]. Although, the ABCD2 score has been used to prognosticate the risk of subsequent stroke [ 4 ], a meta-analysis showed that it does not reliably discriminate patients at low or high risk of recurrent stroke [ 5 ]. Similarly, neuroimaging may enhance the prognostic ability following TIA and minor stroke.…”
Section: Introductionmentioning
confidence: 99%
“…A well-organized rapid access TIA clinic can relocate the care for low to medium-risk TIA patients from an inpatient hospital setting to an outpatient setting. There has been evidence that this practice is safe, cost-effective [[17], [18], [19], [20], [21], [22], [23]], and may improve the outcome [24]. Our results also indicated that only a small number of patients (4.3%) required an intervention or had a diagnosis (atrial fibrillation while on a heart monitor) that could have justified an inpatient hospitalization.…”
Section: Discussionmentioning
confidence: 57%
“…While clinical risk prediction may be used to augment one’s gestalt of a patient’s short-term recurrent stroke risk, it should not be used as the sole determinant of disposition. Adopting a frontloaded, etiology-focused work-up that optimizes individual secondary prevention strategies is likely to be the best approach, regardless of location (hospital, clinic, or observation unit) ( 62 ).…”
Section: Triaging and Dispositionmentioning
confidence: 99%